2019
DOI: 10.3390/cells8050437
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mast Cells in Stroke

Abstract: Mast cells (MCs) are densely granulated perivascular resident cells of hematopoietic origin. Through the release of preformed mediators stored in their granules and newly synthesized molecules, they are able to initiate, modulate, and prolong the immune response upon activation. Their presence in the central nervous system (CNS) has been documented for more than a century. Over the years, MCs have been associated with various neuroinflammatory conditions of CNS, including stroke. They can exacerbate CNS damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 207 publications
(274 reference statements)
1
43
0
Order By: Relevance
“…However, rodent and human mast cells vary in phenotype, the immune response to stimuli, and the spectrum of mediators (pro-and anti-inflammatory) released. Thus, the findings with mast cells in rodents should also be evaluated in patients, as reported previously [13]. Mature mast cells can move from the periphery into the brain under different pathophysiological conditions [13].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, rodent and human mast cells vary in phenotype, the immune response to stimuli, and the spectrum of mediators (pro-and anti-inflammatory) released. Thus, the findings with mast cells in rodents should also be evaluated in patients, as reported previously [13]. Mature mast cells can move from the periphery into the brain under different pathophysiological conditions [13].…”
Section: Discussionmentioning
confidence: 84%
“…Thus, the findings with mast cells in rodents should also be evaluated in patients, as reported previously [13]. Mature mast cells can move from the periphery into the brain under different pathophysiological conditions [13].…”
Section: Discussionmentioning
confidence: 84%
“…Intracranial aneurysm, usually arising in the bifurcation of the cerebral artery, is the result of pathological changes that reduce the tensile strength of the arterial wall and hemodynamic blood flow to which endothelial cells are exposed [17]. It is suggested that mast cells contribute to atherosclerosis and aneurysm formation, which can exacerbate CNS (central nervous system) damage in ischemic and hemorrhagic stroke models by enhancing inflammatory responses and promoting brain-blood barrier disruption, cerebral edema, extravasation, and SAH [18,19]. Moreover, an increase in the level of macrophages, T-lymphocytes, and leukocytes in the wall leads to increased production of ROS, which can modify proteins and lipids, including LDLs (low density lipoproteins), causing atherosclerotic changes in the walls of the vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudo‐allergic reaction could be immediately triggered when contacted with the allergen at the first time and induced a hypersensitivity‐like pathological symptom, such as skin rash, tissue oedema and asthmatic response . Mast cells are the key mediate of allergy and play an important role in the acute hypersensitivity . The laboratory of allergic disease 2 (LAD2) cell line was a kind of human primary mast cell that was always used as response cells in the in vitro allergic reaction study .…”
Section: Introductionmentioning
confidence: 99%